Inclusive Education Practices In Bandung Schools: Policies, Realities, and Aspirations - Ginting, Seriwati; Darmayanti, Tessa Eka; Wianto, Elizabeth; Nurliawati, Nita (Jurnal Pendidikan dan Pengajaran Guru Sekolah Dasar (JPPGuseda), 2025)
Inclusive education was introduced in 2003 as a government initiative to deliver harmonious, equal, and just educational services to Indonesia's heterogeneous population. By 2022, 36,000 educational institutions had embraced it. Regulations are issued regularly to guide its implementation, including Law No. 20 of 2003 on the National Education System (Chapter IV, Articles 5 and 32), Minister of National Education Regulation No. 70 of 2009 on Inclusive Education, and Minister of Education, Culture, Research, and Technology Decree No. 56/M/2022 on Curriculum Implementation Guidelines emphasizing diversification. Examining inclusive education in elementary schools is critical to developing a viable model for its implementation in junior and senior high schools. However, field research demonstrates discrepancies between regulations and real practices. This study focuses on public elementary schools in Bandung, with both education providers and recipients. The research takes a qualitative approach, examining regulations and implementation recommendations for inclusive education in elementary schools. The findings indicate that inclusive education in public elementary schools has not been implemented following rules and guidelines.